Near-monodisperse α-hydroxy and α,ω-dihydroxy amine-based polymers: Synthesis and characterization - Costa, Costas; Patrickios, Costas S. (My University, 1999)
a-Hydroxy anda,v-dihydroxy polymers of 2-(dimethylamino)ethyl methac-rylate (DMAEMA) of various molecular weights were synthesized by group transferpolymerization (GTP) in tetrahydrofuran (THF), using 1-methoxy-1-(trimethylsiloxy)-2-methyl propene (MTS) as the initiator and tetrabutylammonium bibenzoate (TBABB)as the catalyst. The hydroxyl groups were introduced by adding one 2-(trimethylsiloxy)ethyl methacrylate (TMSEMA) unit at one or at both ends of the polymer chain. Theends were converted to 2-hydroxyethyl methacrylate (HEMA) units after the polymer-ization by acid-catalyzed hydrolysis. Gel permeation chromatography (GPC) in THFand proton nuclear magnetic resonance (1H-NMR) spectroscopy in CDCl3were used todetermine the molecular weight and composition of the polymers. These mono- anddifunctional methacrylate polymers can be covalently linked at the hydroxy termini toform star polymers and model networks, respectively.
Keywords: Group transfer polymerization; 2-(dimethylamino)ethyl methacrylate; 2-(trimethylsiloxy)ethyl methacrylate; 2-hydroxyethyl methacrylate; End-functionalpolymers; Telechelics; Polymethacrylates; Water-soluble polymers; Polyelectrolytes; Gels